WASTE HANDLING AND FLY DENSITY LEVELS IN THE TRADITIONAL MARKET OF PALEMBANG, SOUTH SUMATERA - Anggraeni, Anisa; Maksuk, Maksuk; Shobur, Sherli (Indonesia Epidemiological Journal, 2025)
Background: The market is one of the public places with many visitors and the activities of traders and sellers in the market, which indirectly cause waste in the market every day. Most markets produce market waste consisting of wet and dry waste so that during collection, the piles of waste become nests for flies, rats, and insects and become a source of soil, water, and air contamination, and from an aesthetic point of view, they will cause odors and bad views; therefore, it is necessary to manage market waste properly. Purpose: Knowing the handling of waste and the level of fly density in the traditional market of Palembang City in 2023. Methods: This research is descriptive, by means of survey or observation regarding waste handling. The measurement point of fly density was done diagonally with 5 points/market. The total number of points for the four markets is 20 measurement points. Results: The results showed that the sorting of market waste did not meet the requirements, the majority of waste collection did not meet the requirements, waste collection met the requirements, and waste processing did not meet the requirements. The highest average fly density in Pasar Kuto was at point 5 (back left) with an average fly density of 8.2 flies/grill block. Conclusion: Waste handling in 4 Palembang City Traditional Markets is not fully qualified, and the density of flies exceeds the vector quality standard